iMessaging Flesh, Friendship, and Futurities - Coon, Emily; Land, Nicole (Imaginations)

(untitled) (York University, 2019)
This article enacts our ongoing collaborative experiments utilizing “iMessaging” on iPhone as a practice of critical relationality toward building our Indigenous-settler millennial academic friendship. Holding written text alongside our iMessage conversations, we confront three threads that continually interject in our exchanges: (1) what happens with our fleshy bodies when we connect with iMessage; (2) how our co-created, but uncommon, iMessage-body exchanges are an experiment with potential modes of Indigenous-settler academic friendship; (3) and how our iMessaging practice makes real the academic futures that we hope, and need, to contribute to. Together, we grapple with how the iMessaged space we create in our friendship might enable us to be attentive to the disjunctures between Indigenous knowledges and feminist science studies. We wonder how we might think of iMessage as a mode of friendship that is potentially capable of challenging settler-colonial normativities and temporalities of academic relating, while also calling us to attend to the complexities of our bodied lifeworlds as we iMessage our (digital) flesh, futurities, and friendship as young, emerging scholars.